Synchronization of chaotic systems with application to communications - Ji, Yuan (2008)
Chaotic signals generated by chaotic systems are unpredictable and have random noise like property. Such kind of property and the discovery of synchronization of chaos make chaotic secure communication a promising field both in research and in practical applications. In this thesis, the author first proposes a new scheme for the synchronization of a class of chaotic systems by linear matrix inequality method. With this scheme, the condition for impulsive synchronization of chaotic systems is less conservative than those of existing ones and the efficiency of bandwidth utilization is improved.